PENERAPAN PEMBELAJARAN BERBASIS KONVENSIONAL DENGAN TEKNOLOGI INFORMASI PADA TPQ RAUDHATUL ‘ULUM MANYARAN KOTA SEMARANG - Razaq, Jeffri Alfa; Supriyanto, Aji; Budiarso, Zuly; Suharmanto, Eko Taufiq; Kasprabowo, Teguh (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
One of the places for community-based Islamic Religious Education (PAI) is through the Quran Education Park (TPQ). Not all TPQs implement qualified and modern learning methods and media according to the needs of today's education to realize the goals of PAI. The purpose of this service is to realize the goals of PAI at TPQ Raudahtul 'Ulum with conventional-based learning assistance and training methods with Information and Communication Technology (ICT) and digital. Assistance is carried out by installing ICT and digital devices with TPQ teachers. Meanwhile, training is carried out by combining ICT and digital-based learning media with Reading and Writing the Quran (BTA), books and Educational Game Tools (APE) with Islamic themes. The use of a combination of learning media aims to make learning easy, complete, interesting, creative and innovative, and can be done online and students can learn through their own gadgets. As a result, TPQ teachers have become proficient in installing ICT and digital devices and are able to understand and teach combination learning.